Obstetric provider approach to perinatal oral health. - Wilson, Eline H.; Farrell, Chris; Zielinski, Ruth E.; Gonik, Bernard (Journal of Maternal-Fetal & Neonatal Medicine, 2017)
Objective: To examine the practices and attitudes of obstetric providers in the state of Michigan on their approach to perinatal oral health.Methods: An online survey was distributed using health care provider databases in the state of Michigan. Descriptive statistics were tabulated and Fisher's Exact Test was used for categorical variables.Results: There were 146 respondents, 80 obstetrician-gynecologist (OB/GYN) and 66 certified nurse midwife (CNM) providers. Eighty percent acknowledged that perinatal oral health is an important consideration for optimal prenatal care, while only 53% reported having questions specific to oral health on their intake documents. Only 35% discussed oral health, 29% performed an oral cavity exam and 42% recommended oral health assessment by a dentist. CNMs were more likely than OB/GYNs to discuss the importance of oral health (48% versus 24%, (p <.05)) and recommend a formal dental assessment (61% versus 26% (p<.05)). These findings demonstrate a dichotomy of care in that obstetric providers recognize the importance of oral health care in pregnancy, but only a minority routinely incorporates these surveillance practices.Conclusion: These data highlight a gap in obstetric services that needs attention through specific educational initiatives and further research endeavors that address health care provider practice and patient barriers.